Influence of relationship marketing on the organizational results of private educational institutions of Lima metropolitan area (Perú) - Salas Canales, Hugo Jesús (2017)
This research pretends to determine the application of relationship marketing to obtain best organizational results in three private educational institutions. For this, relationship marketing was approached from the following perspectives: Customer loyalty, use of information systems and development of service culture. The type of research was descriptive and the managers of the private educational institutions located in San Juan de Miraflores, San Martín de Porres and Puente Piedra were surveyed, concluding that there is a positive impact of relationship marketing on organizational results.